Selected aspects of quality of intrapartum and postpartum care at primary care level institutions in the Kalutara District and an intervention to improve care - Goonewardana, C.S.E (My University, 2001)
Sri Lanka has a wide network of health institutions in which maternity services are provided. Ten percent of births occur annually in primary care level institutions in the Kalutara district. An assessment of quality of intrapartum care and immediate postpartum care in institutions where specialized services are not available is an important area to be studied. As this area has not received any attention. this study was undertaken to assess some aspects of quality of intrapartum and postpartum care provided to mothers and to can)' out an intervention to assess the effectiveness of the programme to improve care. A baseline assessment was made on the structure. process and outcome. Physical facilities available for providing care to mothers. knowledge on intrapartum and postpartum care was assessed and information on identified practices and skills of care providers was observed. Outcome or pregnancy. postpartum morbidity and mortality of mothers and newborn , were studied in a sample of mothers delivering in these institutions. Observation of skills in resuscitation of the newborn highlighted that the correct technique was deficient. Skills in delivery of a baby were satisfactory except for preparedness for delivery and care of the mother in labour. Routine activities carried out in the antenatal clinic was satisfactory although "other activities" carried out was not satisfactory. Monitoring of a mother on admission to the ward was satisfactory although quality of monitoring a mother during labour was unsatisfactory. Postpartum complications such as PPH and retained placenta were managed without transfer to a higher level institution. Health education given on danger signs during postpartum period was poor. Most mothers were satisfied with the care received